Early diagnosis of congenital hip dislocation - Grosso, Eduardo; Curbelo, Eduardo (Cirugía del Uruguay, 1973)
Diagnosis can be considered "early'.' when established befare the age of six months for the following reasons: 1) Beca use congenital thigh displacements constitute progressive lesions and consequently can be treated in the early stages. 2) Because the younger the patient, the faster the growth potential. 3) Beca use thus it is possible to start treatment befare the child begins to walk. Diagnosis is established through clinic and radiology. Clinic alerts us, X-rays confirm it. Clinic alerts us through good anamenesis -family history with respect to thigh or other displasias, personal history, breech deliveries, difficulty in separating muscles- and correct examination which also evidences other malformations and limitation of muscle abduction or Ortolani's sign. Radiology is of limited value during the first two months. Roof obliquity or methaphyseal separation may be caused by physiological factors or defects in technique. When faced with the slightest clinical suspicion a radiological study should be performed between the ages of 2 to 6 months. Clinics and radiology enable us to establish an early diagnosis and start an early treatment.